Asunercept as an innovative therapeutic approach for recurrent glioblastoma and other malignancies - Krendyukov, Andriy (Cancer Manag Res, 2019)
Glioblastoma is the most common and aggressive malignant tumor of the central nervous system. Despite the existing high unmet medical needs, the past few decades have seen no notable improvement in overall survival for glioblastoma patients. One active area of research to develop new therapeutic options for this disease is focusing on the CD95/Fas receptor and its ligand CD95L/FasL. It is now recognized that in addition to its role in programmed cell death, CD95/CD95L signaling is involved in a wide range of other apoptotic and non-apoptotic pathways directed toward T-effector cells and cells in the tumor microenvironment involved in tumor progression and invasiveness. Asunercept is a first-in-class recombinant glycosylated fusion protein, which has been designed to selectively bind to CD95L and therefore disrupt CD95/CD95L signaling. The current report provides a brief overview of the role of the CD95/CD95L signaling pathway in cancer pathogenesis and discusses how asunercept was designed to bind and neutralize CD95L and disrupt signaling thereby potentially improving outcomes in glioblastoma and other malignancies.